PASSION FOR TEACHING SEBAGAI MODERATOR TERHADAP PEMBERIAN KOMPENSASI DAN LOYALITAS KERJA GURU HONORER DI KARAWANG - Simatupang, Marhisar (Esa Unggul University, 2022)
This research aims to determine the effect of passion for teaching as a moderator on the compensation and work loyalty of honorary teachers in Karawang. This study consists of three variables, namely work loyalty as an endogenous variable, compensation as an exogenous variable and passion for teaching as a moderator variable. The major hypothesis of this study is that there is an effect of compensation on work loyalty moderated by passion for teaching. The number of samples used were 203 honorary teachers in Karawang Regency using the purposive sampling method. Data analysis used a structural equation model (SEM) using partial least squares (PLS). Based on the test results, the hypothetical model has an outer loading value above 0.5 and Cronbach's alpha value for all constructs above 0.5. The standardized root mean square residual (SRMR) is 0.075 or below 0.10 and the normal fit index (NFI) 76% (0.76) is better than the nul model with a chi-square value of 607.903, the majority of the model fit index has met the good fit parameters. This means that the theoretical research model can be accepted as a model that fits the data in the field. The results showed that there was a significant effect of compensation on work loyalty moderated by passion for teaching